Preservation of Local History through the Gayam Heritage Sport Education Program in Gayam Urban Village, Kediri City - Nur Ahmad Muharram; Zainal Afandi; Weda; Budiman Agung Pratama; Gunathevan; Siti Hartini Binti Azmi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The preservation of local history and cultural identity faces challenges due to modernization and the declining interest of younger generations in understanding local heritage. Kelurahan Gayam, Kota Kediri, possesses valuable historical and cultural assets that can be integrated with physical activity programs to strengthen community identity and promote healthy lifestyles. This community service program aimed to empower the community through the Gayam Heritage Sport Education program as an effort to preserve local history, strengthen cultural identity, and increase community physical activity. The program employed the Asset Based Community Development (ABCD) approach involving local government, youth organizations, community leaders, schools, and residents. Activities included local history literacy workshops, heritage walking, traditional games festivals, recreational sports activities, and the development of educational media. The program involved 120 participants consisting of students, youth, and community members. The results showed a significant improvement in local history literacy, with participants’ average knowledge scores increasing from 50% in the pretest to 92% in the posttest, representing a 42% increase. Cultural identity strengthening reached an average score of 87%, with 104 participants reporting a better understanding of local culture after participating in the program. Furthermore, 78.3% of participants (94 individuals) expressed motivation to engage in regular physical activity, while the proportion of participants exercising at least three times per week increased from 35.8% to 78.3%. The program also produced educational outputs, including a local history pocketbook, educational videos, a Heritage Walk map, and a Gayam Heritage Sport Education module. These findings indicate that integrating local history education with recreational sports activities is effective in promoting cultural preservation, community engagement, and healthy lifestyles.